Application of Some Effects on the Degradation of the Aqueous Solution of Fuchsine Dye by Photolysis - Luma Majeed Ahmed (Journal of Global Pharma Technology, 2019)
This manuscript was focused on to how can utilize from UV-A light in order to decolorize the basic fuchsine dye from the aqueous solution at pH 6.4. The produced results from this study were indicated that the acidic medium is favor to decolorize this dye at pH equal to 4.6 and the efficiency of photoreaction increases from 73.75 % to 89.63 % at 70 min. The effect of temperature was done in ranged from (288.15 -333.15) K and occurred that the photoreaction of basic fuchsine dye increases with the increasing the temperature. The activation energy was calculated by depending on Arrihnes equation and found to be 10.286 kJ mol-1. Moreover, the thermodynamics parameters such as ΔH#, ΔS#and ΔG# were measured and given values equal to 7.714 kJ mol-1, -0.00362 kJ mol-1 and 8.923 kJ mol-1 respectively. The positive value of ΔH# enhances the photoreaction of photo-decolorization of this dye. A statistic study was performed by using t-test and F-test, and noticed that there was no significant difference between these methods.Keywords: Basic Fuchsine dye, Photolysis, Rosaniline hydrochloride dye,  PDE and Decolonization.